A Systematic Review of Literature on Recommendation Systems and Machine Learning Applied to Multiagent Systems - Ramos, Karine Pestana; Aguiar, Marilton Sanchotene de (Proceedings of the Workshop-School on Agents, Environments, and Applications (WESAAC); 2020: Proceedings of the 14th Workshop-School on Agents, Environments, and Applications, 2020)
This study developed a systematic review of the literature (SRL), a formal study that is used to map a specific area of knowledge. The main question is defined that will guide the entire search during SRL including other formal steps. This SLR has been defined to synthesize and integrate the areas of multiagent systems, machine learning, and recommendation systems. At the end of the SRL, six studies with different characteristics were found that were adequate to the main question and that satisfy the selection criteria.